Malaria parasites segmentation in red blood cells images using mean-shift and median-cut - Tn. Muda, Tn. Zalizam; A Salam, Rosalina (IEEE Computer Society, 2010)
This paper describes a better approach on merging segmentation algorithms of Mean-shift and Median-cut for color blood cells images. The proposed method applies in two major components of both algorithms. Before starting the analysis, image pre-processing procedure was applied to improve the image before altering the RGB colour space to LUV colour space. After that Mean-shift segmentation will initiate the next process. Since the Means-shift algorithm carry out low level segmentation, some of the region has no semantic meaning. To combat this predicament, median-cut algorithm was introduced to unite the gap left by the meansshift. The results showed better improvement in terms of the contour extraction for further processing.